THE ABILITY OF THE SIXTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP-UR IN CONSTRUCTING COMPARATIVE AND SUPERLATIVE DEGREES - Hartati, Sri; Azhar, Fadly; ', M. Nababan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research was aimed at finding out the ability of the sixth semester students of English Study Program FKIP-UR in constructing comparative and superlative degrees. This research focuses on students’ ability in constructing comparative and superlative degrees based on the form, such as one-syllable adjectives, two-syllable adjectives, adjectives with three or more syllables, irregular adjectives, and adverb. The data were collected using a grammar test. The test contained 20items. The populationwas the sixth semester students of English Study Program FKIP UR in academic year 2016/2017 that consist of 89 students.The sample size was 31 students who are from Class B, chosen by using cluster sampling technique. The needed data were collected by giving grammar test that consist of tables containing data for the students to construct 2 sentences, comparative and superlative degrees in try out and real test.The try out was conducted to check the validity and reliability of the test. Based on the research, it was found out that first: the ability of the second yearstudents in constructing comparative and superlative degrees is in the good level with the mean score of 73.8.Keywords: Ability, Constructing Sentences, Comparative and Superlative Degrees.